2021
DOI: 10.21203/rs.3.rs-600251/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Economic Impact of Switching From Partially Combined Vaccine “Pentaxim ® and Hepatitis B” to Fully Combined Vaccine “Hexaxim ® ” in The Malaysian National Immunization Program

Abstract: Background: The decision to implement new vaccines should be supported by public health and economic evaluations. Therefore, this study was primarily designed to evaluate the economic impact of switching from partially combined vaccine (Pentaxim® plus hepatitis B) to fully combined vaccine (Hexaxim®) in the Malaysian National Immunization Program (NIP) and to investigate healthcare professionals (HCPs)’ and parents/caregivers’ perceptions.Methods: In this economic evaluation study, 22 primary healthcare center… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Studies have similarly demonstrated that parents wish new vaccinations for children to be available in combination form to avoid the extra pain their infants suffer from getting too many shots or injections 37,38 . A study from Malaysia suggested that most parents preferred a combination vaccine to relieve the child's pain and discomfort 22 . The severity of delayed vaccination rises with increasing doses and visits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have similarly demonstrated that parents wish new vaccinations for children to be available in combination form to avoid the extra pain their infants suffer from getting too many shots or injections 37,38 . A study from Malaysia suggested that most parents preferred a combination vaccine to relieve the child's pain and discomfort 22 . The severity of delayed vaccination rises with increasing doses and visits.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 A study from Malaysia suggested that most parents preferred a combination vaccine to relieve the child's pain and discomfort. 22 The severity of delayed vaccination rises with increasing doses and visits. Significantly, the COVID-19 outbreak aggravated this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation